Schaum's outline of calculus - Ayres, Frank, 1901-1994.; Mendelson, Elliott (New York : McGraw-Hill, 2009)
Provides an overview of the fundamentals of calculus and includes 1,105 example problems with step-by-step solutions and explanations of calculator use for solving problems.
Includes index.
Young Adult
Keywords: Calculus -- Outlines, syllabi, etc; Calculus -- Problems, exercises, etc; Calculus -- Outlines, syllabi, etc; Calculus -- Problems, exercises, etc